A Divided Man, a Divided Narrative: An Integrative Sign-Oriented Linguistic and Socio- Psychological Discourse Analysis of Amos’s Text - Perez, Alison; Tobin, Yishai (Narrative Works, 2014)
This paper provides an interdisciplinary discourse analysis of Amos’s life story, utilizing a methodology combining sign-oriented linguistics with a socio- psychological narrative approach. Sign-oriented linguistic theory defines both language and text as supra-systems composed of sub-systems that function as a tool of communication, creating oppositions. Amos’s narrative displays six oppositions: 1) first-person vs. third-person subjects; 2) singular vs. plural subjects; 3) active vs. passive discourse; 4) past vs. present tense; 5) forward- moving chronological vs. arrested presentation of experiences; and 6) thematic oppositions: successes vs. limitations, health vs. illness, expectations vs. disappointments. All oppositions are distinguished by clear discourse markers, reflecting Amos’s worldview and his reciprocal relationship with his surrounding world. We interpret both the form and content of the text, on both the micro and macro levels, in a cohesive manner to produce a comprehensive and holistic analysis—one of the hallmarks of narrative analysis and the narrative paradigm (Spector-Mersel, 2010). Our analysis of the non-random distribution of the content and linguistic forms of Amos’s life story reveal the extra-linguistic message that Amos is a divided man—literally, figuratively, and textually.